Α‐tropomyosin gene (TPM3) mutation in an infant with nemaline myopathy. Issue 3 (3rd February 2021) - Almobarak, Sulaiman; Hu, Jonathan; Langdon, Kristopher D.; Ang, Lee‐Cyn; Campbell, Craig
Abstract: We report a case of neonatal nemaline myopathy with a de novo TPM3 mutation, which has been classified as a likely pathogenic mutation. With the expanding use of genetic testing in congenital myopathies, genotype‐phenotype descriptions of novel variants are important to inform clinical care, diagnosis, genetic counseling, and management of disease. Abstract : We report a case of neonatal nemaline myopathy with a de novo TPM3 mutation, which has been classified as a likely pathogenic mutation. With the expanding use of genetic testing in congenital myopathies, genotype‐phenotype descriptions of novel variants are important to inform clinical care, diagnosis, genetic counseling, and management of disease.